1981
DOI: 10.1128/iai.34.2.347-353.1981
|View full text |Cite
|
Sign up to set email alerts
|

Role of lymphocytes in macrophage-induced killing of Coccidioides immitis in vitro

Abstract: Peritoneal macrophages from normal mice phagocytized arthroconidia and endospores of Coccidioides immitis without affecting the viability of the spores within 4 h after infection. In contrast, macrophages, when infected in the presence of lymphocytes from immune mice, significantly reduced the viability of phagocytized endospores and arthroconidia. The inability of macrophages from normal mice to kill C. immitis may in part be explained by the observation that C. immitis appeared to inhibit fusion of the phago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…If antibody does not play a role in acquired immunity, then perhaps one must postulate a protective role for cell-mediated immunity, as has been clearly demonstrated for coccidioidomycosis (2). The results of the lymphocyte proliferation and footpad assays demonstrated clearly that all six strains were capable of mounting cell-mediated responses to antigens from C. albicans.…”
Section: Discussionmentioning
confidence: 89%
“…If antibody does not play a role in acquired immunity, then perhaps one must postulate a protective role for cell-mediated immunity, as has been clearly demonstrated for coccidioidomycosis (2). The results of the lymphocyte proliferation and footpad assays demonstrated clearly that all six strains were capable of mounting cell-mediated responses to antigens from C. albicans.…”
Section: Discussionmentioning
confidence: 89%
“…However, a significant increase in phagosome-lysosome fusion was observed in macrophages infected in the presence of antigen-activated immune lymphocytes. This correlated with the ability of macrophages to kill C. immitis (3).…”
mentioning
confidence: 82%
“…It was shown that adoptive transfer of resistance to infection with C. immitis was dependent on T lymphocytes from mice immunized with spherule vaccine (4). In vitro, T lymphocytes appeared to promote the antifungal action of macrophages (3). Both arthroconidia and endospores are readily phagocytized by macrophages from normal animals; however, neither are killed.…”
mentioning
confidence: 97%
“…Early data showed that the endospore-containing phagosomes of peritoneal macrophages were not stained with acridine orange, a fluorescent cationic dye, which is an indicator of acidic organelles. 2 In contrast, macrophages obtained from mice vaccinated with formalin-killed spherules stained positively with acridine orange and contained endospores with reduced fungal viability in vitro. 3 The inability of macrophages from nonvaccinated mice to kill endospores has been suggested to be at least partly due to the inhibition of lysosomal fusion, which may explain the negative results of acridine orange staining of the phagocytes.…”
Section: Induction Of Host Arginase I Production Compromises Host Defmentioning
confidence: 97%